Use of prenatal corticosteroids for preterm birth in three Latin American countries - Riganti, Alicia Aleman (2010)
OBJECTIVE: To determine the prevalence of the use of prenatal corticosteroids in women who delivered prematurely in 3 Latin American counties and to evaluate the maternal characteristics associated with use. METHODS: A multicenter, prospective, descriptive study was conducted in 4 hospitals in Ecuador, 5 in Uruguay, and 3 in El Salvador between 2004 and 2008. Women who had delivered between 24 and 34 weeks of pregnancy responded to a questionnaire assessing sociodemographic characteristics, obstetric history, prenatal care, women's attitudes to health services and knowledge of preterm risk factors, prenatal corticosteroid administration, and characteristics of the delivery and neonate. The association between the prenatal corticosteroid use and the study variables was evaluated through a logistic regression analysis based on a hierarchical model. RESULTS: A total of 1062 women who had a preterm birth were included in the study. Prenatal corticosteroid use was 34.8% (95% CI, 29.9%–39.9%) in Ecuador, 54.6% (95% CI, 49.6%–59.6%) in El Salvador, and 71.0% (95% CI, 65.3%–76.2%) in Uruguay. Hospital admission-to-delivery time was associated with the use of prenatal corticosteroids in all 3 countries. CONCLUSION: The study revealed a varied pattern of use of prenatal corticosteroids across the 3 countries, and a diversity of influencing factors.